Respostas
respondido por:
2
D) a3 = a2 + r
5 = a2 + (-1)
5 + 1 = a2
a2 = 6
a2 = a1 + r
6 = a1 + (-1)
6 + 1 = a1
a1 = 7
Logo os 5 primeiros termos da PA sao : 7,6,5,4,3
E) a4 = a3 + r
√2 = a3 + √2
a3 = 0
a3 = a2 + r
0 = a2 + √2
a2 = -√2
a2 = a1 + r
-√2 = a1 + √2
a1 = -2√2
Entao os 5 primeiros termos desta PA sao :
-2√2, -√2, 0 , √2 , 2√2
5 = a2 + (-1)
5 + 1 = a2
a2 = 6
a2 = a1 + r
6 = a1 + (-1)
6 + 1 = a1
a1 = 7
Logo os 5 primeiros termos da PA sao : 7,6,5,4,3
E) a4 = a3 + r
√2 = a3 + √2
a3 = 0
a3 = a2 + r
0 = a2 + √2
a2 = -√2
a2 = a1 + r
-√2 = a1 + √2
a1 = -2√2
Entao os 5 primeiros termos desta PA sao :
-2√2, -√2, 0 , √2 , 2√2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás